Peran Etika dan Tanggung Jawab Sosial dalam Menopang Keberlanjutan Praktik Akuntansi Syariah Modern - Wahyu Ardiman; Roy Sakti Prasetya; Alamsyah Alamsyah; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study discusses the role of ethics and social responsibility in supporting the sustainability of modern Islamic accounting practices amid the dynamic development of the Islamic finance industry. Islamic accounting is not only positioned as a financial recording system, but also as a moral instrument based on the values of justice, trust, transparency, and maqasid al-shariah. This study uses a descriptive qualitative method with a literature review approach through scientific literature, textbooks, and empirical findings related to Islamic accounting ethics, Islamic CSR, Islamic Social Reporting, and green accounting. Data analysis was conducted using content and thematic analysis to identify relevant conceptual and empirical patterns. The results and discussion show that the internalization of Islamic accounting ethics and the integration of Islamic CSR, ISR, and green accounting contribute significantly to strengthening the accountability, transparency, and social legitimacy of Islamic financial institutions. Reporting practices that reflect social and environmental responsibility have been proven to support public trust and institutional sustainability. The conclusion of the study confirms that ethics and social responsibility are the main foundations that ensure the economic, social, and moral sustainability of modern Islamic accounting practices.